Complex Mosaicism of Two Distinct Mutations in a Female Patient With KCNA2-Related Encephalopathy: A Case Report - Gong, Pan; Jiao, Xianru; Zhang, Yuehua; Yang, Zhixian (Frontiers in Genetics, 2020)
KCNA2 gene mutations were described to cause a new molecular entity within the developmental and epileptic or epileptic encephalopathies. Here, we firstly reported a patient with an unusual mosaicism for KCNA2, presenting two distinct mosaic missense mutations at the same loci. Clinical trio-based whole-exome sequencing using next-generation sequencing (NGS) revealed two novel mutations in KCNA2: c.1225A>T (p.(Ile409Phe)) and c.1225A>C (p.(Ile409Leu)). Both missense mutations were in mosaic status and Sanger sequencing confirmed them as de novo. The affected 5-year-old girl presented as seizures with fever sensitivity, and mild cognitive and behavioral disorders. EEG showed focal centrotemporal epileptiform discharges accompanied by nocturnal focal seizures at the age of slightly older than 5 years, more likely carrying a loss-of-function mutation of KCNA2-related phenotype. Further NGS with a mean coverage of 6950× showed 26% (mosaic mutation reads/total reads) of the c.1225A>T mutation and 23% of the c.1225A>C mutation. The sum of their allele fractions was close to 50%, approximately equal to a heterozygous variant. The patient had no seizures for 8 months on combination of levetiracetam (18.75 mg/kg/d) and valproate (20 mg/kg/d) till the last follow-up at the age of 5 years and 11 months. Our findings highlighted the two mosaic mutations responsible for the pathogenesis of KCNA2-related encephalopathy. The patient expanded the mutational spectrum of KCNA2-related encephalopathy and provided new insight into the complex genetic disorder.